Efficient, Large Area, and Thick Junction Polymer Solar Cells with Balanced Mobilities and Low Defect Densities. Issue 3 (29th September 2014) - Armin, Ardalan; Hambsch, Mike; Wolfer, Pascal; Jin, Hui; Li, Jun; Shi, Zugui; Burn, Paul L.; Meredith, Paul
<x xml:space="preserve">Abstract</x> The high power conversion efficiencies (PCEs) of laboratory‐scale polymer‐based organic solar cells are yet to translate to large area modules because of a number of factors including the relatively large sheet resistance of available transparent conducting electrodes (TCEs), and the high defect densities associated with thin organic semiconductor junctions. The TCE problem limits device architectures to narrow connected strips (<1 cm) causing serious fabrication difficulties and extra costs. Thin junctions are required because of poor charge transport (imbalanced mobilities) in the constituent organic semiconductors. These issues are addressed using a combination of approaches to create thick junctions conformally coated on low sheet resistance metal grid TCEs. An essential feature of these thick junctions is balanced carrier mobilities, which affords high fill factors and efficient carrier extraction. Conformal coating is achieved by promoting enhanced intermolecular interactions in the coating solution using a high molecular weight polymeric semiconductor and appropriate solvent system. This combination of balanced mobilities, conformal coating and metallic grid TCEs is a simple and generic approach to the fabrication of defect‐free large area organic solar cells (OSCs). The approach is demonstrated with 25 cm2 monolithic devices possessing aperture‐corrected power conversion efficiencies of 5% and fill factors exceeding 0.5.